2020
DOI: 10.1111/jai.14008
|View full text |Cite
|
Sign up to set email alerts
|

Length‐weight relationship of seven bycatch fish species caught along the Chennai coast, Bay of Bengal, Eastern Indian Ocean

Abstract: Length‐weight relationships (LWRs) were estimated for seven fish species captured as bycatch along the Chennai coast, Bay of Bengal, Eastern Indian Ocean. Fish samples were collected fortnightly between June‐2018 to February‐2019 from the commercial boats operating bottom trawl nets with a cod‐end mesh size of 35mm. The total length (L) and the wet weight (W) to the nearest 0.1 cm and 0.01 g, respectively which is followed by regression analysis. The values of exponent (b) for LWRs varied from 2.5803 (Parachae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In southeast coast of India, coral reefs are mainly located along the Gulf of Mannar and Palk Bay (8°49′–9°l0′N, 79°9′–79°14′E) widening from Thoothukudi to Rameswaram (Pillai, 1996). Hitherto the biological studies of reef‐associated fishes were scanty or limited for several finfishes along the southeast coast of India (Jayaprabha, Purusothaman, & Srinivasan, 2015; Kodeeswaran et al., 2020). The present study provides LWR parameters of eight reef‐associated fish species from the Gulf of Mannar and Palk Bay region.…”
Section: Introductionmentioning
confidence: 99%
“…In southeast coast of India, coral reefs are mainly located along the Gulf of Mannar and Palk Bay (8°49′–9°l0′N, 79°9′–79°14′E) widening from Thoothukudi to Rameswaram (Pillai, 1996). Hitherto the biological studies of reef‐associated fishes were scanty or limited for several finfishes along the southeast coast of India (Jayaprabha, Purusothaman, & Srinivasan, 2015; Kodeeswaran et al., 2020). The present study provides LWR parameters of eight reef‐associated fish species from the Gulf of Mannar and Palk Bay region.…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed that ‘ b ’ values of 3.1215–3.1819 may be considered within the expected range of fishes (Froese, 2006; Sivadas, Sureshkumar, & Kannan, 2020) as different variables including sampling preference such as different fishing gears and mesh size, geographic area, seasons, feeding habits, population, gonad condition, parasitic infection, physiological factors and environmental parameter may affect the outcome of the study (Moutopoulos & Stergiou, 2002). The lower r 2 values in this study might be due to following limitation (a) measurements were made very restricted to narrow size range of these species, where the smaller size classes were missing (b) observation of similar body form during different seasons (Gupta, Sarkar, Bhardwaj, & Pal, 2011) (c) over‐representation of the certain size range (Kodeeswaran et al., 2020) and (d) different geographic collection (Moulitharan et al., 2020). This study can be used to understand the basic biological parameters of these clupeid fishes.…”
Section: Discussionmentioning
confidence: 88%
“…The length‐weight relationships (LWRs) study bestows a baseline information for fishery management in association with several others environmental and population parameters (Froese, 2006; Guo et al., 2019; Kodeeswaran et al., 2020). This has more relevance in commercial fisheries where getting individual weight is rather difficult, though weight is estimated from the length of each individual, which is quite easy to measure (Ricker, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…The coefficient of determination (r 2 ) values in the stilt-root microhabitat were found to be greater than 0,9 in eight out of nine species, which reflect the proper fitness for the growth model and good health status of the fish (Kodeeswaran et al, 2020). Otherwise, the r 2 values in the pneumatophores microhabitat were <0,9 in three out of four species.…”
Section: Discussionmentioning
confidence: 91%